Analysis of Environmental Facilities and Infrastructure in Efforts to Reduce Waste for the Success of the Zero Waste Village Program in RW 13 Mojo Surabaya: Analisis Sarana dan Prasarana Lingkungan dalam Upaya Mengurangi Sampah untuk Keberhasilan Program Kampung Zero Waste di RW 13 Mojo Surabaya - Regita Maharani; Munawar Ali (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Environmental pollution conditions caused by the increasing accumulation of waste have occurred a lot in Indonesia, including in the hero city of Surabaya. Based on data analysis from the Surabaya City Environmental Service, the total waste generation in Surabaya City reaches 1600 tons per day which goes into the Benowo Final Disposal Site (TPA). One of Surabaya City's efforts to reduce and manage waste is by implementing the Zero Waste Village concept. This study focuses on data on facilities and infrastructure in RW 13, Mojo Village, Surabaya to reduce the waste generated. This area was chosen because it has the potential to implement the zerowaste village program to minimize and optimize waste. The amount of waste generation in the RW 13 area of Mojo Village is 140.6 kg/day with an average waste generation per person of 0.052 kg/day. This figure is still below the SNI 8632:2018 standard concerning Procedures for Planning Operational Engineering for Urban Waste Management, namely 0.65 – 0.70 kg/person/day for household waste sources.